Gate dependent phonon shift in tungsten disulfide (WS2) field effect transistor. (4th October 2019) - Iqbal, Muhammad Waqas; Shahzad, Kinza; Hussain, Ghulam; Arshad, Muhammad Kamran; Akbar, Rehan; Azam, Sikander; Aftab, Sikandar; Alharbi, Thamer; Majid, Abdul
Abstract: Graphene is really famous due to its fascinating properties, however the nonexistence of bandgap has roused the interest for other 2D materials that have some bandgap. Transition metal dichalcogenides (TMDCs), on the other hand are the promising alternatives. Raman spectroscopy is an easy, nondestructive and fast technique to examine TMDCs. Here we report on the gate dependent Raman spectra of tungsten disulfide (WS2 ) field effect transistor. Raman Spectra of WS2 sample shows two major peaks E2g (in-plan mode) at 356 cm −1 and A1g (out of plan mode) at 420 cm −1, respectively at zero gate voltage. However, by increasing the positive gate voltage (Vbg ) upto 50 V, the peak position of A1g mode moves towards the lower wavenumber by 3.8 cm −1 and the FWHM of A1g mode is also increased by value of 4.2 cm −1 . Conversely, the A1g mode moves towards the higher wavenumber (3.1 cm −1 ) by increasing the negative Vbg to −50 V and FWHM of A1g mode is decreased by 1.3 cm −1 . The peak intensity ratio of A1g and E2g modes is increased by increasing the positive Vbg and is decreased by increasing the negative Vbg . Furthermore, the transvers and I-V characteristic curves of WS2 device indicated that WS2 is an n-type material. The ON/OFF ratio is calculated as to be 4.56 × 10 6 for our WS2 device and the mobility is 37 cm 2 V −1 s −1 .